2019
DOI: 10.3390/d11120225
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Hemiptera in Southwest Cameroon: Biodiversity of Potential Reservoirs of Mycobacterium ulcerans and Multiple Wolbachia Sequence Types Revealed by Metagenomics

Abstract: Buruli ulcer (BU), caused by Mycobacterium ulcerans, is a neglected tropical disease associated with freshwater habitats. A variety of limnic organisms harbor this pathogen, including aquatic bugs (Hemiptera: Heteroptera), which have been hypothesized to be epidemiologically important reservoirs. Aquatic Hemiptera exhibit high levels of diversity in the tropics, but species identification remains challenging. In this study, we collected aquatic bugs from emerging foci of BU in the Southwest Region of Cameroon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 107 publications
0
7
0
1
Order By: Relevance
“…These taxa have also been previously associated with both aquatic and terrestrial insects [ 46 , 47 , 48 , 49 , 50 , 51 ], suggesting that they are a common component of the microbiome of insects in general, and play important functional roles in their insect hosts [ 3 , 6 , 46 , 52 ]. For example, a recent study found that the genus Wolbachia is widespread in aquatic Hemipteran, including Gerridae, from Southwest Cameroon [ 53 ]. In addition, the genera Wolbachia and Spiroplasma are known to influence host ecology and evolution [ 1 , 3 , 6 , 53 ], and could be involved in diversification in water striders (see below).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These taxa have also been previously associated with both aquatic and terrestrial insects [ 46 , 47 , 48 , 49 , 50 , 51 ], suggesting that they are a common component of the microbiome of insects in general, and play important functional roles in their insect hosts [ 3 , 6 , 46 , 52 ]. For example, a recent study found that the genus Wolbachia is widespread in aquatic Hemipteran, including Gerridae, from Southwest Cameroon [ 53 ]. In addition, the genera Wolbachia and Spiroplasma are known to influence host ecology and evolution [ 1 , 3 , 6 , 53 ], and could be involved in diversification in water striders (see below).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study found that the genus Wolbachia is widespread in aquatic Hemipteran, including Gerridae, from Southwest Cameroon [ 53 ]. In addition, the genera Wolbachia and Spiroplasma are known to influence host ecology and evolution [ 1 , 3 , 6 , 53 ], and could be involved in diversification in water striders (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the studies carried out, very few have been conducted on aquatic insects and even fewer on marine insects. However, two recent studies conducted in Cameroon [ 18 ] and Panama [ 19 ] looking for the bacterial community in the Gerridae and Veliidae found Wolbachia in these taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Few recent studies demonstrated the presence of Wolbachia in semiaquatic bugs. In Cameroon, Esemu et al (2019) detected Wolbachia in freshwater insects that represent a potential reservoir for the bacterium Mycobacterium ulcerans MacCallum, 1948 causing Buruli ulcer. This research focused on nine species of the Gerridae Leach, 1815 and Veliidae Amyot & Serville, 1843 families including the three genera Limnogonus, Microvelia, and Rhagovelia [18].…”
Section: Introductionmentioning
confidence: 99%